China and North Korea : strategic and policy perspectives from a changing China - Freeman, Carla P. (Carla Park), 1962- (New York, NY : Palgrave Macmillan, 2015)
'At a time when China's historically close'as lips and teeth' relations with North Korea appear to be changing, this volume provides unique access in English to the diverse perspectives informing China's North Korea policy and insights into how Chinese specialists assess a country that, while both its neighbor and ally, is also a threat to international security and China's national interests. The editor has gathered original essays by some of today's leading Chinese experts on China's foreign policy toward North Korea, the history of Beijing's relations with Pyongyang, and North Korea's politics and economy. Contributors include scholars from China's elite universities and think tanks in Beijing, as well as from provinces bordering North Korea'--
Keywords: Security, International -- China; National security -- China; China -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- China; China -- Politics and government